PERAN MEDIA SOSIAL INSTAGRAM DALAM PEMBENTUKAN IDENTITAS KEWARGANEGARAAN - Nur Arba Asari; Siregar, Delila Maya Sari; Gajahmanik, Shelly Elprida; Pulungan, Nabila Amanda; Manik, Asianna; Sri Yunita (STAI Nurul Falah Airmolek, 2024)
In the midst of the rapid flow of information and digital connectivity, social media has become a public space that is inseparable from modern human life. Platforms like Instagram allow us to connect with people from all over the world instantly. This makes it easier for us to maintain relationships with friends and family, even if they are physically far from us. More than just an information channel, Instagram also has the potential to be an effective tool for instilling the values of civic identity. The method that the author uses in this research is a qualitative method using library research, namely conducting research by collecting information from books and journals. The aim of this research is to see how social media can influence citizenship identity. The results of this research show that the role of Instagram in forming civic identity is very complex and influenced by various factors such as consumer content, social interactions, and government regulations. Keywords: Social Media, Instagram, Citizenship Identity